Clonación, secuenciación y caracterización molecular de genes codificantes de polifenol oxidasa (PPO) en Theobroma cacao L. (cacao) en el cantón Quevedo-Provincia de Los Ríos - Acosta Farías, Jenny Milena (2017)
In Ecuador, cocoa plantations often present low yields due to a great diversity of pathogens, especially Moniliophthora roreri (monilia), which cause a substantial infection. It is thought that the fungi attack and an uprising of expression levels of encoding polyphenol oxidases (PPOs) genes are related as a defense mechanism in the presence of pathogens and herbivores in different plants. In order to identify the encoding genes of PPOs, leaves of National cocoa, coming from resistant and susceptible plants were collected, located in “La Represa”, property of Universidad Técnica Estatal de Quevedo. An extraction protocol for total RNA for recalcitrant cocoa leaves was optimized. After its reverse-transcription to cDNA, amplifying PCR assays were performed with different primers, designed from conserved PPOs sequences. Amplifying products allowed to identify a gen of 961 bp, similar to a gene that encodes a predicted PPO from Theobroma cacao stored in NCBI (XP_017978715.1). In addition to identify the gen, it is fundamental to evaluate in the future expression levels and quantify them in different development fruit stages. This quantification will be important not only to propose tools for monilia control but also to enhance genetic improvement of National cocoa.